2013
DOI: 10.1080/1331677x.2013.11517620
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Markets Hypothesis: Empirical Evidence from Montenegro Equity Market

Abstract: In this paper we examined adaptive markets hypothesis (AMH) using three factors we assumed that affect weak-form of market efficiency: observation period, time horizon represented by rolling window sizes and data aggregation level. We have analyzed market value weighted index MONEX20, which is proxy from Montenegro equity market, over 2004-2011 period. Rolling window analysis with fixed parameter in each window is employed to measure the persistence of deviations from a random walk hypothesis (RWH) over time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Studies conducted in other markets also find support from AMH, such as Popovic, Mugosa, and Durovic (2013), Urquhart and Hudson (2013), Ghazani and Araghi (2014), Dourado and Tabak (2014), Su arez, Duarte, and Ort ız (2015), Verheyden, De Moor, and Bossche (2015), Hiremath and Narayan (2016), Urquhart and McGroarty (2016), Okorie and Lin (2021), and Munir, Sukor, and Shaharuddin (2022). These studies suggest different impacts by macroeconomic and institutional incentives on market efficiency, suggesting that factors other than economic ones may affect market efficiency over time, and differently, depending on the stimulus level and macroeconomic environment.…”
Section: Adaptive Markets Hypothesis (Amh)mentioning
confidence: 86%
“…Studies conducted in other markets also find support from AMH, such as Popovic, Mugosa, and Durovic (2013), Urquhart and Hudson (2013), Ghazani and Araghi (2014), Dourado and Tabak (2014), Su arez, Duarte, and Ort ız (2015), Verheyden, De Moor, and Bossche (2015), Hiremath and Narayan (2016), Urquhart and McGroarty (2016), Okorie and Lin (2021), and Munir, Sukor, and Shaharuddin (2022). These studies suggest different impacts by macroeconomic and institutional incentives on market efficiency, suggesting that factors other than economic ones may affect market efficiency over time, and differently, depending on the stimulus level and macroeconomic environment.…”
Section: Adaptive Markets Hypothesis (Amh)mentioning
confidence: 86%
“…Otherwise, it can be inferred that the efficiency of the relevant market is consistent with the implications of the EMH. In the existing literature, a large number of studies have reported that the efficiency of various financial markets is time-varying consistent with the implications of the AMH (see, for example, Lo, 2004;Lim et al, 2013;Popović et al, 2013;Ghazani and Araghi, 2014;Verheyden et al, 2015;Ito et al, 2016;Noda, 2016;Charles et al, 2017;Rahman et al, 2017;Chu et al, 2019;Jiang and Li, 2020;Noda, 2020). These studies report time-varying return predictability by examining only price movements.…”
Section: Zamanla Değişen Getiri öNgörülebilirliği Ve Adaptif Piyasalar Hipotezi: Yeni Bir Yaklaşım Olan Wild Bootstrap Olabilirlik Oranı mentioning
confidence: 96%
“…However, it has been explained that the time-varying feature complies with the AMH. Also, Popović et al (2013) applied the Runs test within the moving sub-sample approach to the Montenegro MONEX20 index data of 2004-2011 to investigate the market efficiency over time and the result of the analysis confirmed the AMH. Urquhart & Hudson (2013) studied the validity of the AMH for the stock markets of the US, UK, and Japan with long-term historical data.…”
Section: Literature Reviewmentioning
confidence: 97%